A hierarchical VN/Co3ZnC@NCNT composite as a multifunctional integrated host for lithium–sulfur batteries with enriched adsorption sites and accelerated conversion kinetics. Issue 38 (7th September 2022) - Fu, Junjie; Shen, Zewei; Cai, Daoping; Fei, Ban; Zhang, Chaoqi; Wang, Yaguang; Chen, Qidi; Zhan, Hongbing
Abstract : A space-confined melamine-assisted nitridation strategy is developed to synthesize the hierarchical VN/Co3 ZnC@NCNTs composite, which can serve as a multifunctional integrated sulfur host for lithium–sulfur batteries. Abstract : Lithium–sulfur (Li–S) batteries are growing in popularity by virtue of their high energy density, low cost and environmental friendliness. However, the commercialization of Li–S batteries is severely hindered by low sulfur utilization, sluggish sulfur redox chemistry, and the severe shuttle effect of lithium polysulfides (LiPSs). In this work, a hierarchical composite composed of VN and nitrogen-doped carbon nanotubes encapsulated with Co3 ZnC nanoparticles (denoted as VN/Co3 ZnC@NCNTs) is conceptually designed through a space-confined melamine-assisted nitridation strategy. As a multifunctional integrated sulfur host, the hierarchical VN/Co3 ZnC@NCNT composite has a variety of advantages including high electrical conductivity, good physical confinement and chemical adsorption to LiPSs, and superior electrocatalytic activity, which can effectively facilitate the immobilization–diffusion–conversion process of soluble LiPSs. As a result, the Li–S batteries based on the VN/Co3 ZnC@NCNT host exhibit a high discharge capacity of 1399.4 mA h g −1 at 0.1C, as well as excellent rate capability (566.4 mA h g −1 at 5C) and long-term cycling stability (557.6 mA h g −1 at 1C after 500 cycles with a low decay rate of 0.064% per cycle). More encouragingly, even at a high sulfur loading of 4.5 mg cm −2, the S@VN/Co3 ZnC@NCNT cathode still delivers a high reversible capacity of 639.2 mA h g −1 at 0.2C after 100 cycles. Furthermore, experimental results and theoretical calculations demonstrate that strengthening adsorption is not responsible for the improvement of catalytic activity. This work could provide a novel insight into the rational development of multifunctional integrated sulfur host materials for high-performance Li–S batteries.